Thiol-Responsive Gold Nanodot Swarm with Glycol Chitosan for Photothermal Cancer Therapy - SeongHoon Jo; In-Cheol Sun; Wan Su Yun; Jinseong Kim; Dong-Kwon Lim; Cheol-Hee Ahn; Kwangmeyung Kim (Molecules, 2021)
Photothermal therapy (PTT) is one of the most promising cancer treatment methods because hyperthermal effects and immunogenic cell death via PTT are destructive to cancer. However, PTT requires photoabsorbers that absorb near-infrared (NIR) light with deeper penetration depth in the body and effectively convert light into heat. Gold nanoparticles have various unique properties which are suitable for photoabsorbers, e.g., controllable optical properties and easy surface modification. We developed gold nanodot swarms (AuNSw) by creating small gold nanoparticles (sGNPs) in the presence of hydrophobically-modified glycol chitosan. The sGNPs assembled with each other through their interaction with amine groups of glycol chitosan. AuNSw absorbed 808-nm laser and increased temperature to 55 °C. In contrast, AuNSw lost its particle structure upon exposure to thiolated molecules and did not convert NIR light into heat. In vitro studies demonstrated the photothermal effect and immunogenic cell death after PTT with AuNSW. After intratumoral injection of AuNSw with laser irradiation, tumor growth of xenograft mouse models was depressed. We found hyperthermal damage and immunogenic cell death in tumor tissues through histological and biochemical analyses. Thiol-responsive AuNSw showed feasibility for PTT, with advanced functionality in the tumor microenvironment.